2018
DOI: 10.1055/a-0612-7887
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement for Contrast-Enhanced Ultrasound (CEUS)-Based Standardized Algorithms for the Diagnosis of Hepatocellular Carcinoma in High-Risk Patients

Abstract: Interobserver agreement is better for ESCULAP than for CEUS-LI-RADS. This is mostly due to the fact that perception of contrast washout varies between different observers. However, interobserver agreement is good for arterial phase hyperenhancement, which is the key diagnostic feature for the diagnosis of HCC with CEUS in the cirrhotic liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Significant heterogeneity was observed in the current metaanalysis of CEUS LI-RADS for HCC and OM. Although the nonthreshold effect did not differ in multiple and single reviewer studies, some studies [21,22] showed that the interobserver agreement regarding CEUS LI-RADS was fair and noted that disagreements were mostly due to different perceptions of washout because CEUS is an imaging modality that depends greatly on the physician's clinical experience. However, the study conducted by Schellhaas et al [13] concluded that the sensitivity of CEUS could improve if "washout" was omitted as a diagnostic criterion.…”
Section: Discussionmentioning
confidence: 95%
“…Significant heterogeneity was observed in the current metaanalysis of CEUS LI-RADS for HCC and OM. Although the nonthreshold effect did not differ in multiple and single reviewer studies, some studies [21,22] showed that the interobserver agreement regarding CEUS LI-RADS was fair and noted that disagreements were mostly due to different perceptions of washout because CEUS is an imaging modality that depends greatly on the physician's clinical experience. However, the study conducted by Schellhaas et al [13] concluded that the sensitivity of CEUS could improve if "washout" was omitted as a diagnostic criterion.…”
Section: Discussionmentioning
confidence: 95%
“…In distinction to the late enhancement on CECT or CEMRI, ICC has a variety of patterns in the AP at CEUS but all show washout in the LP [59,113,127]. The typical pattern of malignancy is better displayed by CEUS than by CECT or CEMRI [128,129].…”
Section: Cholangiocarcinoma (Intrahepatic Cholangiocellular Carcinomamentioning
confidence: 97%
“…The title and abstract review identified 578 studies, of which 20 full text articles were reviewed (Table ), yielding 14 articles for potential inclusion. Of these, 10 articles 10‐19 were included in the analysis. We also identified one conference abstract from online archives that provided sufficient data for inclusion 20 .…”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are presented in Table 1. The 11 studies 10‐20 included a total of 5535 observations with 3983 HCCs. The methodological quality of the studies, which was assessed by the Quality Assessment of Diagnostic Accuracy Studies‐2, is summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%